2022
DOI: 10.1186/s12885-022-09205-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the value of amide proton transfer-weighted imaging and diffusion kurtosis imaging in evaluating the histological grade of cervical squamous carcinoma

Abstract: Background Uterine cervical cancer (UCC) was the fourth leading cause of cancer death among women worldwide. The conventional MRI hardly revealing the microstructure information. This study aimed to compare the value of amide proton transfer-weighted imaging (APTWI) and diffusion kurtosis imaging (DKI) in evaluating the histological grade of cervical squamous carcinoma (CSC) in addition to routine diffusion-weighted imaging (DWI). Methods Forty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The degree of tumor differentiation is a prognostic factor of CSC, especially during the early stages of the disease. The higher the pathologic tumor grade, the worse the degree of differentiation, the easier for the tumor to locally invade and form distant metastases, the higher the recurrence rate, the worse the prognosis, and the lower the survival rate (2)(3)(4)(5). Histopathologic tumor types, the degree of tumor differentiation, and the stages of cervical cancer are key factors when choosing a treatment plan and assessing prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of tumor differentiation is a prognostic factor of CSC, especially during the early stages of the disease. The higher the pathologic tumor grade, the worse the degree of differentiation, the easier for the tumor to locally invade and form distant metastases, the higher the recurrence rate, the worse the prognosis, and the lower the survival rate (2)(3)(4)(5). Histopathologic tumor types, the degree of tumor differentiation, and the stages of cervical cancer are key factors when choosing a treatment plan and assessing prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The DKI model reflects the non-Gaussian diffusion property caused by the microstructural complexity of tissues and therefore has the potential in quantifying the microstructural heterogeneity of tissues [ 11 , 12 ]. The DKI parameter MK is reported to positively correlate with the heterogeneity of tissue microstructure, while MD represents how freely water can diffuse through a tissue, with lower MD indicating impaired diffusion and probably denser tissue [ 27 ]. In this study, CC with higher tumor grade and advanced FIGO stage presented significantly higher MK and lower MD.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant difference was not observed between the low grade and high grade CC in this study. The reason may be that only the patients with CSC were included in previous studies [ 27 , 32 , 33 ], while in this study, the patients with CA were not excluded. CA originates from endocervical cells and therefore has rich glandular structure and the ability to secrete mucin.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer (UCC) was the fourth most commonly diagnosed malignancy and the fourth leading cause of cancer death among women worldwide [13,[173][174][175][176][177][178]. Cervical squamous carcinoma (CSC) is the most common pathological type of UCC, accounting for 75-80% of the total number of cervical cancer patients [170]. Poorly differentiated CSCs can easily cause local invasion and distant metastasis, influencing the choice of treatment and patient prognosis.…”
Section: Other Fieldsmentioning
confidence: 99%
“…Therefore, it is important to accurately assess the degree of CSC before treatment. Hou et al compared the weighted imaging value for amide proton transfer (APTWI) and DKI in evaluating the histological grade of cervical squamous carcinoma (CSC) in addition to DWI [170]. They showed that the APTWI (MTRasym) parameters and MK values of G1 were significantly lower than those of G2 and those parameters of G2 were significantly lower than those of G3.…”
Section: Other Fieldsmentioning
confidence: 99%